Comparison of slope failure areas between limit equilibrium method and smoothed particle hydrodynamics. Issue 2 (25th January 2022) - Chu, Xuesong; Li, Liang; Yu, Guangming; Yuan, Changfeng
Abstract: The determination of slope failure areas plays an important role in slope stability problem. The previous studies evaluate the failure area either based on the slip surface with minimum factor of safety (FS) or using area failure probability method (AFPM). A user-defined displacement criterion is combined with smoothed particle hydrodynamics (SPH) to properly quantify the failure area and to rationally assess the average slope failure area using Monte Carlo Simulation (MCS). The proposed method is illustrated through two slope examples. It is found that although AFPM can identify the multiple slip surfaces, it tends to overestimate the area of failed soil mass due to its inability to consider the progressive behaviour of a slope failure. A wider search range for entrance and exit points in AFPM is highly recommended. The slip surface with minimum FS underestimates the area of failed soil mass because only initial slip surface is identified and used while neglecting the evolution of a slope failure. The proposed approach serve as an alternative tool for quantifying the average slope failure area accounting for the specific acceptable threshold displacement value, d, or dimensionless coefficient, ξ . As the d or ξ value increases, the average slope failure area decreases.